Convergent evolution links molybdenum insertase domains with organism-specific sequences - Miriam Rabenow; Eduard Haar; Katharina Schmidt; Robert Hänsch; Ralf R. Mendel; Kevin D. Oliphant (Communications Biology)
Abstract In all domains of life, the biosynthesis of the pterin-based Molybdenum cofactor (Moco) is crucial. Molybdenum (Mo) becomes biologically active by integrating into a unique pyranopterin scaffold, forming Moco. The final two steps of Moco biosynthesis are catalyzed by the two-domain enzyme Mo insertase, linked by gene fusion in higher organisms. Despite well-understood Moco biosynthesis, the evolutionary significance of Mo insertase fusion remains unclear. Here, we present findings from Neurospora crassa that shed light on the critical role of Mo insertase fusion in eukaryotes. Substituting the linkage region with sequences from other species resulted in Moco deficiency, and separate expression of domains, as seen in lower organisms, failed to rescue deficient strains. Stepwise truncation and structural modeling revealed a crucial 20-amino acid sequence within the linkage region essential for fungal growth. Our findings highlight the evolutionary importance of gene fusion and specific sequence composition in eukaryotic Mo insertases.